2007
DOI: 10.1016/j.jada.2007.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Polyamine Database for Assessing Dietary Intake

Abstract: Reducing the concentration of polyamines (spermine, spermidine, and putrescine) in the body pool may slow the cancer process. Because dietary spermine, spermidine, and putrescine contribute to the body pool of polyamines, quantifying them in the diet is important. Limited information about polyamine content of food is available, especially for diets in the United States. This brief report describes the development of a polyamine database linked to the Fred Hutchinson Cancer Center food frequency questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
82
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 15 publications
7
82
3
1
Order By: Relevance
“…As far as diet is concerned, poly-amine content is high in several food products including fruits, cheeses and meat. Again, high concentrations of putrescine can be found in common diets, particularly in orange and grapefruit juice (111).…”
Section: Influence Of Dietary Polyamines On Crc Chemopreventionmentioning
confidence: 99%
“…As far as diet is concerned, poly-amine content is high in several food products including fruits, cheeses and meat. Again, high concentrations of putrescine can be found in common diets, particularly in orange and grapefruit juice (111).…”
Section: Influence Of Dietary Polyamines On Crc Chemopreventionmentioning
confidence: 99%
“…Other studies have also addressed the importance of vegetables as an important source of PAs in the human diet. 11,30,31 Both free and conjugated PA content should be considered in the dietary intake estimation; thus, the total (free + conjugated) Put, Spd, and Spm mean content was calculated and discussed. A general trend was observed: A 1 lettuces contributed to the highest daily intake of PAs (3.81, 0.36, and 0.44 μmol/day for Put, Spd, and Spm, respectively), while A 2 lettuces contributed to the lowest daily intake of PAs (2.36, 0.22, and 0.32 μmol/day for Put, Spd, and Spm, respectively).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We observed a partial rebound in putrescine levels at 12 months, but levels remained approximately 50% below those found at baseline. Putrescine is the most prevalent dietary polyamine (44) and is the preferred substrate for the polyamine transport system (45). A study in patients with prior colorectal adenomas found that putrescine levels rebounded in normal rectal mucosa after 12 months of continuous low-dose DMFO (500 mg/d), suggesting an adaptive response to prolonged ODC suppression with a compensatory cellular uptake of diet-or bacteria-derived putrescine (46).…”
Section: Discussionmentioning
confidence: 99%